2017
DOI: 10.5502/ijw.v7i3.642
|View full text |Cite
|
Sign up to set email alerts
|

An anthropological examination of virtues and character strengths and wellbeing: Imagining a good life in professional training

Abstract: Since its inception, there has been a rapid growth in the number of studies on Peterson and Seligman's ( 2004) classification of Positive Psychology's (PP) strengths and virtues, linking them to wellbeing (Brdar & Kashdan, 2010). However, some authors have criticized this approach (Schwartz & Sharpe, 2006), arguing that this classification does not integrate a complete understanding of the Aristotelian virtue of practical wisdom. Building on this critique, the article aims to apply the theoretical framework of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Many conceptual writings and empirical studies have demonstrated how the AT.9 not only embraces paradox, but can assess the unconscious (non-rational) dimension of one’s imagination, worldview and symbolical capacity. For instance, the relevance of the ASI and/or AT.9 have been conceptually and empirically demonstrated in the context of resilience and spirituality ( Bellehumeur, 2011 ; Nguyen et al, 2018 ; Bellehumeur and Carignan, 2021 ; Yeung and Bellehumeur, 2021 ), wellbeing, virtues, as well as personal strengths ( Bellehumeur et al, 2017 ). The conceptual and empirical adequacy of the ASI and the AT.9 have also been shown in the context of the paradoxical dimension of boundaries in psychotherapy, theology, and anthropology ( Bellehumeur and Chambers, 2017 ; Bellehumeur, 2020 ; Kam and Bellehumeur, 2020a , b ); along with various concepts associated with interpersonal styles as well as and marital, family, and psychotherapeutic relationships ( Bellehumeur et al, 2013 ; Bellehumeur, 2014a , b ; Bellehumeur and Carignan, 2018 ).…”
Section: Conscious and Unconscious Integrative Complexitymentioning
confidence: 99%
“…Many conceptual writings and empirical studies have demonstrated how the AT.9 not only embraces paradox, but can assess the unconscious (non-rational) dimension of one’s imagination, worldview and symbolical capacity. For instance, the relevance of the ASI and/or AT.9 have been conceptually and empirically demonstrated in the context of resilience and spirituality ( Bellehumeur, 2011 ; Nguyen et al, 2018 ; Bellehumeur and Carignan, 2021 ; Yeung and Bellehumeur, 2021 ), wellbeing, virtues, as well as personal strengths ( Bellehumeur et al, 2017 ). The conceptual and empirical adequacy of the ASI and the AT.9 have also been shown in the context of the paradoxical dimension of boundaries in psychotherapy, theology, and anthropology ( Bellehumeur and Chambers, 2017 ; Bellehumeur, 2020 ; Kam and Bellehumeur, 2020a , b ); along with various concepts associated with interpersonal styles as well as and marital, family, and psychotherapeutic relationships ( Bellehumeur et al, 2013 ; Bellehumeur, 2014a , b ; Bellehumeur and Carignan, 2018 ).…”
Section: Conscious and Unconscious Integrative Complexitymentioning
confidence: 99%